AS PARCERIAS PÚBLICO-PRIVADAS NA EDUCAÇÃO INFANTIL: UM ESTUDO SOBRE A LAICIDADE DO ESTADO E A RELIGIOSIDADE DE INSTITUIÇÕES CONVENIADAS - Almeida, Volnei Bispo de (2014)
One of the policies most used by the municipal public power to guarantee educational services to children 0-3 years and increasing the number of vacancies in kindergartens has been the adoption of partnerships through agreements with private institutions. Many questions emerge from this public policy, for example, the relationship between the secular state and the religiosity of many of these institutions. This study arose from the need to provide greater transparency and broaden the debate on the agreements between the municipal government and aid agencies, especially regarding the conflict between the public and the private, between the secular and the religious. This study aimed to investigate public-private partnerships and the possible impacts on the secular state and the right to education. The research problem posed was what the CME Paper 12/2011 revealed about the secular state and the religiosity of partner institutions in the care of early childhood education in São Bernardo do Campo. There was the assumption that the representation of a convening authority to the Municipal Board of Education on spiritual education express a possible religious education projection in public kindergarten. The theoretical discussion involved as authors FISCHMANN (2009), ARELARO (2008), SARMENTO (2006), ADRIÃO (2009), OLIVEIRA (2005) and ideas that dealt with the deformations of public and private interests, the supply of places following daycare, religious instruction in public schools. The methodology used was to analyze literature and documents. The literature shows a historical subordination of public early childhood education to private welfare and disputes over implementation of religious education in public basic education. The documents analyzed revealed that there may be some degree of involvement of the secular state when it formalizes partnerships with charities of religious origin, especially when evaluating the shortcomings and trends of management and supervision of agreements made by the government. It is believed that this study opens the doors to investigate policies and practices that are facing or stimulating religious education in public schools and covenanted day cares.